Evaluation of acepromazine and butorphanol as preanaesthetics agent in tiletamine-zolazepam induced anaesthesia in dogs undergoing ovariohysterectomy: a perspective study on clinical, physiological, haemodynamic and haematobiochemical parameters - Manjusha, K.M.; Kinjavdekar, P.; Amarpal; Kumar, Rohit; Islam; Aakanksha; Pawde, A.M.; Saxena, A.C.; De, U.K. (Indian Journal of Veterinary Surgery, 2025)
This study aimed to evaluate the preanaesthetic efficacy of a combination of acepromazine and butorphanol in dogs induced with tiletamine-zolazepam and maintained under isoflurane anaesthesia for elective ovariohysterectomy. A prospective clinical trial was conducted on 12 healthy adult female dogs of various breeds and ages, randomly divided into two groups (n=6). All dogs received atropine sulphate (0.045 mg/kg body wt., i.m.) as premedication. After 5 min, group I animals received acepromazine (ACP) alone (0.03 mg/kg body wt., i.m.), while group II received a combination of ACP (0.03 mg/kg body wt.) and butorphanol (BUT) (0.2 mg/kg body wt.). Anaesthesia was induced by intravenous administration of tiletamine-zolazepam (TZ) until the desired effect was achieved, followed by maintenance with isoflurane (ISO) at a vaporizer setting of 1-2%. The anaesthetic combinations were compared based on clinical, physiological, haemodynamic, haematological, and biochemical parameters. ACP administered intramuscularly before TZ produced only mild sedation, poor muscle relaxation, and inadequate analgesia. The combination of ACP and BUT produced better sedation, analgesia, and muscle relaxation. Further, analgesia was more consistent when BUT was combined with ACP.